1988
DOI: 10.1002/sim.4780070906
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome of anaesthesia in patients over 40 years: A multifactorial risk index

Abstract: The prediction of outcome of anaesthesia in patients over 40 years of age was assessed using a multifactorial index based on current preoperative factors recorded prospectively. The study was conducted using a representative sample of anaesthetizations (except for cardiac surgery) including 517 cases with major complication (occurring during or within 24 hours of anaesthesia) and a one in fifty random sample comprising 1538 cases without complication. A split sample approach was adopted and a logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
5

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 21 publications
(1 reference statement)
0
53
0
5
Order By: Relevance
“…There have been several other large studies of outcome after anaesthesia [1][2][3][4]. These were established primarily to estimate important predictors of outcome [2][3][4] and also to compare various anaesthetic techniques [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several other large studies of outcome after anaesthesia [1][2][3][4]. These were established primarily to estimate important predictors of outcome [2][3][4] and also to compare various anaesthetic techniques [4].…”
Section: Discussionmentioning
confidence: 99%
“…These were established primarily to estimate important predictors of outcome [2][3][4] and also to compare various anaesthetic techniques [4]. Gender has not been found to be a significant predictor of mortality or severe morbidity, though Forrest et al [4] found that males were more likely to have severe postoperative respiratory complications and Warden et al [1] found a preponderance of males in their mortality figures, though they did not adjust for patient and surgical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a combination of age, sex, physical status score, length of operation (as a proxy for surgical severity), and emergency status; these variables had been identified earlier as factors of significance to anaesthetic outcomes. [22][23][24] Further refinements in case-mix description will be necessary before more precise comparisons of outcome of anaesthetic care are possible. Nonetheless, it is unlikely that the five-fold magnitude of the differences seen here can be explained by lack of adjustment for yet to be defined variables.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical patients are at higher risk of having complications for a variety of reasons, including ASA (American Society of Anesthesiologists) class, 72 [84][85][86] type of anesthesia, 73,78,87,88 and other comorbidities-especially chronic obstructive pulmonary disease, coronary artery disease, and renal failure. 79,80,89 The risk of postoperative complications also depends on the type of surgery.…”
Section: Evidence On Sleep Apnea As a Risk Factor For Perioperative Cmentioning
confidence: 99%